Investigating the Symmetric Effects of Working Capital on Profitability in Turkish Banking: an ARDL Empirical Analysis - Raza, Ali; Tursoy, Turgut; Shaikh , Erum; Shaikh, Ahsan-ul-Haque (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2024)
This paper carried out an empirical study on Return on Assets (ROA), total assets turnover, financial leverage, working capital, and debt-to-equity ratio. This study investigated commercial banks operating in Turkey. A secondary data collection method is used for the data collected from fifteen commercial banks. These banks' financial reports were examined from 2011 to 2022. A line graph is presented for each balance that tells us the volatility ratio in the variables, the unit root test applied to resolve the unit root problem, and the cointegration test used for long-term relationships among variables. The Autoregressive Distributed Lag (ARDL) bound test was performed to measure the short-run and long-run effects. Financial leverage, debt-to-equity ratio, and working capital have short- and long-run effects on ROA. Total asset turnover has only long-run effects on ROA in the Turkish banking industry. This study will be beneficial for investment managers, financial specialists, treasurers, and controllers of the banking industry.